Merajut Harmoni Sosial Melalui Karawitan: Upaya Membentuk Karakter Berbudaya dan Cinta Tanah Air pada Siswa di SMA Yayasan Atikan Sunda Bandung - Restuna Nur Inten; Bagja Waluya; Mirna Nur Alia Abdullah (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The preservation of local culture faces serious challenges amidst the current of globalization that has the potential to weaken the cultural identity and national values ​​of the younger generation. Schools have a strategic role in instilling cultural character and love of the homeland through contextual educational activities, one of which is traditional arts extracurricular activities. This study aims to describe the forms of social interaction in gamelan extracurricular activities, the process of forming social harmony, and the formation of cultural character and love of the homeland in high school students of Yayasan Atikan Sunda Bandung. The study used a qualitative approach with descriptive methods. Data were collected through observation, interviews, and documentation of instructors, trainers, and student members of the gamelan extracurricular, then analyzed through data reduction, data presentation, and drawing conclusions based on George Herbert Mead's Symbolic Interactionism theory. The results of the study indicate that social interaction is built through communication, cooperation, and mutual assistance between students, which forms social harmony in the form of togetherness, tolerance, and solidarity. Gamelan activities also contribute to forming cultural character and fostering a sense of love of the homeland through pride and concern for the preservation of national culture.